Do radionuclide and echocardiographic techniques give a universal cut off value for left ventricular ejection fraction that can be used to select patients for treatment with ACE inhibitors after myocardial infarction?. Issue 5 (May 1995) - Ray, S. G.; Metcalfe, M. J.; Oldroyd, K. G.; Pye, M.; Martin, W.; Christie, J.; Dargie, H. J.; Cobbe, S. M.
Abstract : OBJECTIVE–To determine whether echocardiography and radionuclide angiography give comparable results when the left ventricular ejection fraction is measured early after myocardial infarction and thus whether, irrespective of the method used, a single value for the ejection fraction could be used as a guide for starting treatment with an angiotensin converting enzyme inhibitor. DESIGN–Prospective comparison of measurement of left ventricular ejection fraction by echocardiography and radionuclide angiography. SETTING–Coronary care units of two university teaching hospitals in Glasgow. PATIENTS–99 patients studied within 36 hours of acute myocardial infarction. OUTCOME MEASURES–Left ventricular ejection fraction assessed by echocardiography and radionuclide angiography. RESULTS–70 (77%) of the 99 patients had ejection fraction measured by both echocardiographic and radionuclide techniques, 30 in centre 1 and 40 in centre 2. In centre 1 the mean difference (SD) in ejection fraction (radionuclide angiography–echocardiography) was -8 (10%); 95% CI -12 to -4%. In centre 2 the mean difference was -14 (11%); 95% CI -17 to -11%. If patients had been treated with an ACE inhibitor on the basis of a radionuclide ejection fraction of < 40% then 93% in centre 1 (28 of 30) and 98% in centre 2 (39 of 40) would have been treated. This compares with 63% (19 of 30) and 50% (20 of 40), respectively if echocardiography had been used as a guide. CONCLUSION–Measurement of ejection fraction is highly dependent on the method used and it is therefore impossible to quote a universally applicable figure for left ventricular ejection fraction below which an ACE inhibitor should be used after myocardial infarction.